ANALISIS PENERAPAN DISIPLIN SEKOLAH SISWA KELAS XI SMA SANTUN UNTAN PONTIANAK - Dani Dani; Sulistyarini Sulistyarini; Achmadi Achmadi (Universitas Tanjungpura, 2019)
AbstractThis study aims to determine (1) the form of the application of time discipline, (2) the role of the teacher in implementing the school discipline, and (3) the driving and inhibiting factors in the implementation of time discipline and discipline in enforcing school rules in class XI of SMA Santun Untan Pontianak. The descriptive research method with the qualitative form was used in this study. The data were collected by observation technique, interview, and documentation. The results showed that the school discipline has not been optimally implemented and has several obstacles. The implementation of school discipline includes teachers and students being on time, students reading books for 10 minutes before the learning process begins, students collecting assignments on time, and teachers implementing school rules and giving penalties to students who violate the school rules. The inhibiting factors in implementing the school discipline are the lack of awareness of students about the importance of discipline such as students who keep coming late to school even though they have been reprimanded and sanctioned by the teacher, inadequate school facilities and infrastructure, and the lack of several teachers’ roles in controlling students at school. Keywords: Implementation, School Discipline